Voltage-current characteristics of metal oxide varistors for low voltage telephone lightning protector under the application of multiple lightning impulse - Yaacob, M.M.; Ghani, R.A. (1998)
Surges resulting from lightning strikes could propagate not only into the power line but also into a low voltage line such as the telecommunication system and could cause damage to the equipment. In order to protect this highly sensitive equipment, a telephone lightning protector (MOV) has to be installed in the telephone set. Since the natural characteristics of lightning are a multiple stroke/flash, the response of the protector under this condition has to be investigated. This paper presents the experimental studies on the voltage and current characteristic of the MOV under the application of multiple lightning impulse voltage and current